REDESAIN TRACER (OUTGUIDE) PADA PENYIMPANAN DOKUMEN REKAM MEDIS DI KLINIK RAWAT INAP MITRA HUSADA MAGETAN - Adisya Putri Maharani; Dea Allan Karunia Sakti (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2023)
The results of the research that the researchers did at the Mitra Husada Magetan Inpatient Clinic on the use of tracers in the failling room. The researchers saw that the tracer used was still using cardboard covered with paper so that it was easy to tear and slip, this caused difficulties in retrieving medical record documents. The tracer is an important tool to monitor the use of medical records. The tracer currently used at the Husada Magetan partner inpatient clinic uses paper taped to cardboard. it is known that the medical record tracer needs to be redesigned after being seen from various aspects. This study aims to redesign the medical record tracer at the Mitra Husada Magetan inpatient clinic. The type of research used in this research is descriptive qualitative. Data was collected by observing using a check list and open interviews. Data analysis used descriptive analysis. the clinic does not have an officer who handles medical records so they do not know the soup and are constrained by costs. The redesign of the medical record tracer is very important because it makes it easier for officers to make returns.